An Information System Using Design Thinking and Agile–DevSecOps Based on Website (Case Study: Kute Rumah Bundar, Ketambe, Southeast Aceh) - Muhamad Ramadan; Diva Vionita; Siti Rahmayani; Eki Aryadi (Jurnal Armada Informatika, 2026)
Village-government digitalization often stops at information publication and does not yet integrate citizen needs, administrative workflows, and secure software operations. This study develops a website-based information-system design for Kute Rumah Bundar, Ketambe, Southeast Aceh, by combining Design Thinking, Agile, and DevSecOps. An artifact-oriented design approach is used. The service context is represented through a problem map, actor needs, service scenarios, architecture, product backlog, access-control matrix, threat model, and acceptance criteria. Design Thinking maintains alignment with citizen and staff needs; Agile translates those needs into measurable increments; and DevSecOps embeds security checks throughout software change. The result comprises five service domains, eighteen core requirements, four user roles, three development increments, and twelve security-risk scenarios. Traceability inspection shows that every core requirement is mapped to a module and acceptance criterion, while each risk scenario is connected to preventive, detective, or recovery controls. The combined approach therefore produces a design that is user-centered, incrementally deliverable, and secure by design. The main contribution is an integrated working pattern that can be replicated for digital service transformation in resource-constrained village administrations.